Improving The Vibration Damping In A Real Marine Propulsion System Using Solidworks - صالح, الهادي (Latakia University Journal -Engineering Sciences Series, 2025)
Marine propulsion systems are the core components of a ships, however, vibrations caused by operations can lead to structural problems and inefficient performance. Therefore, vibration damping is an important aspect to ensure the safety and efficiency of these systems. Vibration damping in marine propulsion systems is a vital area that requires continuous research and technological development to ensure sustainable and safe performance. By improving damping techniques, which enhance the efficiency of marine plants and achieve better results in the field of renewable energy. This research designed a propulsion station for a real ship 3D using SolidWorks program and then conducted virtual modeling of the vibratory response Both the propeller shaft and the medium shaft at two rotation speeds (nominal speed and speed during takeoff) for both displacement and speed and acceleration of vibration as vibration inducing forces arise from pulse forces in engine cylinders as well as from the propeller. These results were compared with the requirements of the BRC, after which many ways in which vibratory response is controlled and adjusted to remain within permissible limits.